Reliability and validity of a novel tool to comprehensively assess food and beverage marketing in recreational sport settings - Rachel J. L. Prowse; Patti-Jean Naylor; Dana Lee Olstad; Valerie Carson; Louise C. Mâsse; Kate Storey; Sara F. L. Kirk; Kim D. Raine (BMC, 2018)
Abstract Background Current methods for evaluating food marketing to children often study a single marketing channel or approach. As the World Health Organization urges the removal of unhealthy food marketing in children's settings, methods that comprehensively explore the exposure and power of food marketing within a setting from multiple marketing channels and approaches are needed. The purpose of this study was to test the inter-rater reliability and the validity of a novel settings-based food marketing audit tool. Methods The Food and beverage Marketing Assessment Tool for Settings (FoodMATS) was developed and its psychometric properties evaluated in five public recreation and sport facilities (sites) and subsequently used in 51 sites across Canada for a cross-sectional analysis of food marketing. Raters recorded the count of food marketing occasions, presence of child-targeted and sports-related marketing techniques, and the physical size of marketing occasions. Marketing occasions were classified by healthfulness. Inter-rater reliability was tested using Cohen's kappa (κ) and intra-class correlations (ICC). FoodMATS scores for each site were calculated using an algorithm that represented the theoretical impact of the marketing environment on food preferences, purchases, and consumption. Higher FoodMATS scores represented sites with higher exposure to, and more powerful (unhealthy, child-targeted, sports-related, large) food marketing. Validity of the scoring algorithm was tested through (1) Pearson's correlations between FoodMATS scores and facility sponsorship dollars, and (2) sequential multiple regression for predicting "Least Healthy" food sales from FoodMATS scores. Results Inter-rater reliability was very good to excellent (κ = 0.88-1.00, p < 0.001; ICC = 0.97, p < 0.001). There was a strong positive correlation between FoodMATS scores and food sponsorship dollars, after controlling for facility size (r = 0.86, p < 0.001). The FoodMATS score explained 14% of the variability in "Least Healthy" concession sales (p = 0.012) and 24% of the variability total concession and vending "Least Healthy" food sales (p = 0.003). Conclusions FoodMATS has high inter-rater reliability and good validity. As the first validated tool to evaluate the exposure and power of food marketing in recreation facilities, the FoodMATS provides a novel means to comprehensively track changes in food marketing environments that can assist in developing and monitoring the impact of policies and interventions.